2015
DOI: 10.1002/cctc.201500310
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Support Properties for Immobilization or Purification of Enzymes

Abstract: Immobilization and purification of enzymes are usual requirements for their industrial use. Both purification and immobilization have a common factor: they use a solid activated support. Using a support for enzyme purification means having mild conditions for enzyme release and a selective enzyme–support interaction is interesting. When using a support for immobilization, however, enzyme desorption is a problem. The improvement of enzyme features through immobilization is a usual objective (e.g., stability, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
387
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 504 publications
(407 citation statements)
references
References 240 publications
4
387
0
2
Order By: Relevance
“…However, the use of the immobilized lipase offers some aspects of greater interest, that is, it protects the biocatalyst from the reaction medium, maintains the enzyme activity and allows the reuse of the system. 7,8,11,13 Wang et al 30 performed the resolution of (R,S)-menthol using various lipases, acyls donors and supports for immobilization. The results showed that when the reaction was carried out using valeric acid as a donor acyl and lipase from Candida rugosa immobilized in DEAR-Sephadex A-25 as catalyst, the conversion, ee p and E% values were of 44, 95 and 87%, respectively.…”
Section: Influence Of Lipase Immobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of the immobilized lipase offers some aspects of greater interest, that is, it protects the biocatalyst from the reaction medium, maintains the enzyme activity and allows the reuse of the system. 7,8,11,13 Wang et al 30 performed the resolution of (R,S)-menthol using various lipases, acyls donors and supports for immobilization. The results showed that when the reaction was carried out using valeric acid as a donor acyl and lipase from Candida rugosa immobilized in DEAR-Sephadex A-25 as catalyst, the conversion, ee p and E% values were of 44, 95 and 87%, respectively.…”
Section: Influence Of Lipase Immobilizationmentioning
confidence: 99%
“…Basically, the methods of immobilization may be divided into four types, namely adsorption on a solid support, entrapment, encapsulation and crosslinking. [9][10][11][12][13] Natural polymers, such as starch, cellulose, agarose and gelatin, have been used in the preparation of supports for the immobilization of enzymes. These are an attractive alternative from an economic point of view and they can be obtained from renewable sources and are biodegradable, making them more environmentally acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…Immobilization is localization of enzyme molecules in/on a solid support for continuous catalytic process and it is an effective method to improve almost all the enzyme properties, if properly designed 5,6 . The support is one of the major component of an immobilized enzyme system [7] . The characteristics of the support are of paramount importance in determining the performance of the immobilized enzyme system 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…The support is one of the major component of an immobilized enzyme system [7] . The characteristics of the support are of paramount importance in determining the performance of the immobilized enzyme system 7,8 . An ideal support require some properties like high mechanical stability, hydrophobicity, biocompatibility, inertness toward enzymes, resistance to bacterial attacks and availability at low cost are the important 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation